Using the terrestrial laser scanning technique for aeolian sediment transport assessment in the coastal zone in seasonal scale. (31st July 2019) - Danchenkov, Aleksandr; Belov, Nikolay; Stont, Zhanna
Abstract: Based on an analysis of a series of digital elevation models obtained using a terrestrial laser scanning (TLS) technique, assessment of mean sand transport rate was performed in seasonal scale. Analytical procedures based on the method of finite differences were performed to quantify the volume of moved material. Coastal hydrodynamic processes, as well as the meteorological regime were taken into account as forcing or limiting factors of aeolian processes. The TLS method is successfully used to assess variability and embryo dunes formation in different areas by other researchers. Two characteristic coastal areas on the territory of the Сuronian Spit National Park in Southeastern Baltic Sea were selected as key sites for morphodynamic processes studying. The results of the analysis of coastal hydrodynamic and related morphodynamic processes show that only one site is suitable for estimating the average rate of sand transport on a seasonal scale. The received relationship between cross-shore mean sand transport rate and the cross-shore directions average wind speed are in a good agreement with the Bagnold formula and with field measurements using sand traps. Extreme hydrodynamic situations leading to beach inundation, as well as precipitation, limit the development of aeolian processes on a seasonal scale.